Analgesic efficacy and safety of paracervical block versus conscious sedation in the surgical evacuation of the uterus following first-trimester incomplete miscarriages: A randomised controlled trial - Nnenna A Nweke; Chidebe Christian Anikwe; Richard L Ewah; Osita S Umeononihu; Justus N Eze (SAGE Open Medicine, 2022)
Objective: To compare the analgesic efficacy and safety of paracervical block and conscious sedation in the surgical evacuation of the uterus following a first-trimester miscarriage. Methods: This is an open-label, randomised control trial comparing pain relief by paracervical block versus conscious sedation during manual vacuum aspiration of first-trimester incomplete miscarriages. One-hundred and sixty-two women were equally randomised into two groups. Group A (paracervical group) received a paracervical block of 4 ml of lidocaine each at the 4 and 8 o’clock positions. Group B (conscious sedation group) received intravenous 30 mg pentazocine and 10 mg diazepam. Data obtained were presented using a frequency table, student t-test, chi-square and Mann–Whitney test and bar chart. A P-value of ⩽0.05 was taken to be statistically significant. Results: The mean pain score was lower in the paracervical block group compared to the conscious sedation group (P < 0.05); however, there was no significant difference in women’s satisfaction between the groups (P ⩾ 0.05). Conscious sedation had more negative side effects compared to paracervical block which was significant (P < 0.05). Conclusion: Paracervical block has better pain control compared with conscious sedation and has a good side effect profile. Trial registration: Pan African Clinical Trial Registry (registered trial no. PACTR202108841661192). Synopsis Paracervical block for manual vacuum aspiration (MVA) during first-trimester miscarriage is associated with less pain among women compared with conscious sedation.